Curriculum framework to facilitate critical thinking skills of undergraduate nursing students: A cooperative inquiry approach - Christian Makafui Boso; Anita S. van der Merwe; Janet Gross (Wiley, 2023)
Abstract Aim Critical thinking (CT) is vital in assisting nurses to function efficiently in the ever‐changing health care environment. A CT‐based curriculum framework provides the impetus necessary to drive the acquisition of CT skills of students. Yet, there is no known CT‐based framework contextualized to developing countries where seniority tradition is a norm. Therefore, the aim of this study was to develop a CT‐based curriculum framework to facilitate the development of CT skills of nursing students in developing countries. Design Cooperative inquiry. Methods Using purposive sampling, 11 participants comprising students, educators and preceptors developed a CT‐based curriculum framework. Results Findings were organized into a framework illustrating interconnected concepts required to foster CT skills of nursing students. These concepts include authentic student-facilitator partnership, a facilitator that makes a difference; a learner that is free to question and encouraged to reflect; a conducive and participatory learning environment; curriculum renewal processes and contextual realities.